Pengaruh Metode Pelaksanaan Terhadap Kinerja Waktu Proyek Rekonstruksi Jembatan di Kota Palu - Fahirah, F.; Hilmansyah, T.; Salsabila, Z. (Tadulako University, 2025)
The bridge reconstruction project is an effort to rebuild bridges that have been destroyed by the earthquake and tsunami that hit Palu City. The implementation of the bridge reconstruction project has complicated work that raises an analysis of the effect of the bridge project implementation method on project time performance. The purpose of this study was to determine the effect of implementation methods on the time performance of the bridge reconstruction project in Palu City. The sample of this study amounted to 22 workers on the bridge reconstruction project using Purposive Sampling method. The field collection process was carried out by collecting primary data in the form of interviews and distributing questionnaires. The data were processed using descriptive statistics and multiple linear regression analysis. The results of this study indicate that partially of the five variabels affecting the implementation method, the material factor variabel has a significant effect on the time performance of the bridge reconstruction project. While simultaneously work methods, labor, material factors, equipment, and project site conditions have an effect of 8,988 with a significant 0.000 on the variabel time performance of the bridge reconstruction project in Palu City.